Proposal for a Model of Teaching Digital Competencies for Distance, Open and Online Education of the UNED, Costa Rica (Revista Electrónica Calidad en la Educación Superior, 2023)
Based on a qualitative research with a descriptive scope, a documentary analysis was conducted on the topic of digital competencies. The results were organized in a matrix and then systematized to continue with the study and its application in the teaching work context through the selection of seven models that have a wide trajectory in the pedagogical field. Once the key concepts were defined and the relevant theoretical connections about distance, open and online education were established, a model of digital teaching competencies was elaborated for this educational modality. This seeks to strengthen the figure of the teacher, whose work cannot be paralyzed and much less displaced by the lack of knowledge in a specific educational modality or the implementation of the various technological tools available today, as happened with COVID-19.
Keywords: Educational model; Teacher; Educational technology; Digital competences; education